Piezoelectric Bimorph Cantilever for Vibration-Producing-Hydrogen - Zhang, Jun (MDPI, 2012)
A device composed of a piezoelectric bimorph cantilever and a water electrolysis device was fabricated to realize piezoelectrochemical hydrogen production. The obvious output of the hydrogen and oxygen through application of a mechanical vibration of ∼0.07 N and ∼46.2 Hz was observed. This method provides a cost-effective, recyclable, environment-friendly and simple way to directly split water for hydrogen fuels by scavenging mechanical waste energy forms such as noise or traffic vibration in the environment.